Near infrared two photon imaging using a bright cationic Yb(iii) bioprobe spontaneously internalized into live cells. Issue 44 (18th May 2017) - Bui, Anh Thy; Beyler, Maryline; Grichine, Alexei; Duperray, Alain; Mulatier, Jean-Christophe; Guyot, Yannick; Andraud, Chantal; Tripier, Raphaël; Brasselet, Sophie; Maury, Olivier
Abstract : An Yb(iii ) complex based on a dimethyl cyclen macrocyclic ligand is used as two-photon NIR bioprobe. Abstract : An Yb(iii ) complex based on a dimethyl cyclen macrocyclic ligand functionalized by charge transfer antennae was prepared. This cationic [YbL 3 ] + complex is stable and soluble in water and presents interesting photophysical nonlinear properties. It is spontaneously internalized and accumulates in live cells. High quality images have been obtained both in a classical NIR-to-vis configuration and in the more challenging NIR-to-NIR one.